Testimonies of the socio-cultural and historical facts of nuestra senora de las angustias - Quinto-Vinas, Maricon M. (San Miguel, Iriga City: University of Saint Anthony, 2018)
Testimonies of the socio-cultural and historical facts of nuestra senora de las angustias.
Includes bibliographical references.
English
Keywords: History